Sifat Organoleptik, Kandungan Zat Gizi, Dan Daya Terima Iwel Latan Untuk Makanan Tambahan Ibu Hamil - Zuhria Handayani; Made Darawati; I Gde Narda Widiada (Jurnal Gizi Prima (Prime Nutrition Journal), 2019)
Background :In Indonesia there are still many cases of Chronic Energy Deficiency caused by imbalance of nutrients, especially in energy and protein intake, so that the nutrients needed by the body are not fulfilled. Efforts that can be done to prevent chronic energy shortages in pregnant women is to provide alternative food supplements in the form of nutrient dense snacks, one of which is iwel which is added with high-protein legumes namely soybeans which are then made into soy flour. Iwel with the addition of soybean flour is expected to meet the requirements as PMT for pregnant women. Iwel is a traditional food that is popular with many people, has a soft texture like dodol and is classified as semi-wet food. This study aims to determine the organoleptic properties, nutrient content, and acceptability of Iwel Latan for pregnant women.Research Methods:The experimental research method with a completely randomized one-factor design, namely the addition of soy flour consisting of 5 treatment levels 10%, 15%, 20%, 25%, 30%.Research result:The results showed that Iwel Latan with the addition of 25% (t4) soybean flour from the weight of the entire selected ingredient to the best treatment level and the addition of soy flour significantly affected the texture of Iwel Latan (p <0.005). The content of Iwel Latan nutrients is 40.71% moisture content, 1.60% ash content, 9.39% protein, 3.89% fat, and 44.40% carbohydrate.Conclusion: The nutrient content of Iwel Latan is higher when compared to PMT biscuits which are usually given to pregnant women Chronic Energy Deficiency.The acceptance of pregnant women is 30 people, of which 25 pregnant women receive well (83%) and 5 pregnant women receive less (17%).